Implementation of the Bengkulu–Taba Penanjung Toll Road Development - Kader, Bando Amin C; Saputra, Harius Eko; IS, Tuti Handayani (Journal of Research in Social Science and Humanities, 2022)
This study aims to analyze the implementation of land acquisition policy in the construction of the Bengkulu–Taba Penanjung toll road using George C. Edward III’s policy implementation model, which includes the dimensions of communication, resources, disposition, and bureaucratic structure. A descriptive qualitative approach was used, with data collected through in-depth interviews, observations, and documentation. The findings reveal that although the policy implementation followed formal regulations such as Presidential Regulation No. 148 of 2015 and Government Regulation No. 19 of 2021, practical challenges remain in the field. One-way communication, limited resources, rigid implementers, and suboptimal interagency coordination were identified as major barriers. Resistance from the affected communities was observed, largely due to compensation perceived as below market value and lacking recognition of the land’s emotional significance. These findings highlight the need for participatory approaches and two-way communication in the implementation of land-based public policies.